2020
DOI: 10.1007/jhep07(2020)106
|View full text |Cite
|
Sign up to set email alerts
|

Non-perturbative approaches to the quantum Seiberg-Witten curve

Abstract: We study various non-perturbative approaches to the quantization of the Seiberg-Witten curve of N = 2, SU(2) super Yang-Mills theory, which is closely related to the modified Mathieu operator. The first approach is based on the quantum WKB periods and their resurgent properties. We show that these properties are encoded in the TBA equations of Gaiotto-Moore-Neitzke determined by the BPS spectrum of the theory, and we relate the Borel-resummed quantum periods to instanton calculus. In addition, we use the TS/ST… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
116
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(119 citation statements)
references
References 105 publications
3
116
0
Order By: Relevance
“…We have also shown that the X-cluster variables correctly reproduce the ones of the four-dimensional BPS quivers under a suitable scaling limit. It would be very interesting to further explore the relation of our results with the ones on exact WKB methods and TBA equations [56,66,67], possibly extending these methods to the q-difference/5d case. For the class S theories, an important rôle should be played by the group Hitchin system [68], in the perspective of its quantization [69,70].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…We have also shown that the X-cluster variables correctly reproduce the ones of the four-dimensional BPS quivers under a suitable scaling limit. It would be very interesting to further explore the relation of our results with the ones on exact WKB methods and TBA equations [56,66,67], possibly extending these methods to the q-difference/5d case. For the class S theories, an important rôle should be played by the group Hitchin system [68], in the perspective of its quantization [69,70].…”
Section: Discussionmentioning
confidence: 88%
“…A first instance of this phenomenon was discussed from the mathematical perspective in [55]. For the case at hand, the non-trivial relation between the two approaches is encoded in a suitable limit of blow-up equations [43,[56][57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…The specific choice of prefactor in (3.29) ensures a simple form of large θ asymptotic behavior for X: In [41,42] it was noticed that the Floquet exponent in the context of N = 2 SYM coincides with the A-cycle period a.…”
Section: Explicit Demonstration Of the Numerical Approachmentioning
confidence: 99%
“…To complete this computation we use the formula from [13] and transform it to more convenient form using (B. 21 5 Spectral theory meaning of quasiclassical conformal blocks…”
Section: Jhep12(2020)125mentioning
confidence: 99%
“…2η ∈ Z, one gets only decaying solution at z → ∞. Hence, to get normalizable solution of (2.15) one has to impose the condition 2η = k ∈ Z, see also [21,22]. Taking into account (2.43) we see that this condition is nothing but the quantization condition [17] ∂F ∂σ ∈ 2πiZ.…”
Section: Jhep12(2020)125mentioning
confidence: 99%